India's economic diplomacy at the United Nations - Tawale, S. N. (Meerut, 1975)
This study focuses its attention on India's role in promoting international economic cooperation under the UN auspices. The UN concerns itself with a wide variety of international economic issues ranging from occasional measures like relief to the drought stricken people, to those of fundamental nature, e. g. restructuring of international monetary system. The most pervading theme in the UN today, however, is the development of under-developed countries. It is therefore within this setting that the present study examines India's participation in the UN economic bodies at the policy-making level. The purpose is to attempt a sketch of the essential traits of India's approach in the field. Here again, attention is confined to three areas viz. technical assistance, development finance and inter national trade. The other areas such as the role of multi-national corporations, international food assistance etc. are excluded from the study not because they are less vital to the interests of the under developed countries, but because the same set of assumptions of UN economic diplomacy prevail there too, thus making no material difference to the purpose and scheme of the book. The study covers the deliberations of three UN policy-making organs namely, General Assembly, ECOSOC and UNCTAD, and spans a period of almost three decades, starting from the Bretton Woods Conference and ending up with the Santiago Session of UNCTAD.
Keywords: Diplomacy